Appropriate traction can help identify the optimal dissectable layer for infrapyloric lymph node dissection in laparoscopic gastrectomy. Issue 1 (7th July 2020) - Miura, Susumu; Hosogi, Hisahiro; Kawada, Hironori; Ito, Takeshi; Okada, Toshihiro; Okumura, Shintaro; Shimoike, Norihiro; Akagawa, Shin; Yamaura, Tadayoshi; Yoshimura, Fumihiro; Kanaya, Seiichiro
Abstract: Introduction: Appropriate dissection of the infrapyloric lymph nodes (no. 6 LNs) is important in gastric cancer surgery. In laparoscopic surgery, dissection of the no. 6 LNs along the inner dissectable layer from the left side of patient has been reported. However, it is difficult for surgeons to provide appropriate traction with their left hand from the left side. To resolve this difficulty, we dissected the no. 6 LNs from the patient's right side to identify the optimal layer. We then evaluated the oncologic reliability of the layer and the safety of this procedure. Methods: From the patient's right side, the surgeon used their left hand to provide appropriate traction when pulling the adipose tissue, including the no. 6 LNs. This exposed the optimal layer between the adipose tissue and the pancreas. To assess this maneuver, the surgical outcomes of patients who underwent laparoscopic distal gastrectomy from April 2011 to March 2013 were retrospectively analyzed. The surgical outcomes included the number of the no. 6 LNs resected, time to dissect the no. 6 LNs, incidence of pancreatic complications, and recurrence in the no. 6 LNs. Results: There were 112 patients identified. The median number of the no. 6 LNs resected was five. The median time to dissect the no. 6 LNs was 14 minutes. Four patients developed pancreatic fistula, and another four patients developed intra‐abdominal abscess. There was no recurrence in the no. 6 LNs. Conclusion: The optimal layer was oncologically reliable, and these procedures were safe.